ANALISIS SWOT TERHADAP OPTIMALISASI REKOMENDASI OMBUDSMAN DALAM GANTI RUGI PELAYANAN PUBLIK - Asep Cahyana (STISIP Widyapuri Mandiri, 2023)
Equality between providers and users in public services is characterized by the opportunity for users to file objections, complaints, and claims for compensation. In Indonesia, policies regarding compensation are contained in various laws and regulations, including Law 25/2009 on Public Services and Law Number 37/2008 on the Ombudsman of the Republic of Indonesia. However, after thirteen years, the compensation policy based on the Public Service Law has not been implemented because the implementing regulations are not yet complete. As an alternative, the compensation mechanism through Ombudsman recommendation based on Ombudsman Law needs to be studied in depth. In this paper, the author uses a simple SWOT analysis to analyze the strengths, weaknesses, opportunities, and threats for which the Ombudsman recommendation are optimized to resolve people complaint containing demand for compensation. This study uses a qualitative approach. Data were obtained from interviews, observations, books, scientific journals, institutional information/documents, and online news articles. Data were analyzed using an interactive modeling approach and N-Vivo software. A number of important findings and recommendations are presented in this paper.